Peran Pendidik dalam Menumbuhkan Motivasi Belajar Peserta Didik Kesetaraan di SKB Cerme Kabupaten Gresik - Sopinah, Adinda Kusdwiyanti; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
This study aims to analyze the role of educators in increasing student learning motivation in the equivalency program at SKB Cerme, Gresik Regency. The study used a qualitative approach with descriptive methods. Data collection was conducted through observation, interviews, and documentation involving educators and students. The results of the study indicate that educators have a very important role as motivators, facilitators, and guides in the learning process. Educators are able to provide encouragement, create an interesting learning atmosphere, and help students overcome various learning difficulties they face. Student learning motivation is influenced by supporting factors, such as a conducive learning environment and positive social relationships, as well as inhibiting factors, such as fatigue, limited time, and minimal social support. Optimizing the role of educators has been proven to increase student activeness and attendance in learning. Therefore, the implementation of innovative, adaptive, and humanistic learning strategies is needed to improve the quality of equitable education in a sustainable manner.